"Two contrasted vies of empire : Herodotus on Easter empires and Thucydides on Athenian empire" - Saïd, Suzanne (My University, 2014)
Our word ' empire' is a derivative of the latin imperium. However it is worth looking at the vocabulary and description of the Eastern empires proposed by Herodotus for the Eastern empires and (from Croesus, the Medes and the Persians) and confront it with Thucydides' presentation of the contemporary Athenian empire.
Ciclo de Conferencias Octubre 2014, con ayuda del Vicerrectorado de Investigación de la UMA. Facultad de Filosofía y Letras. Departamento de Filología Griega, Estudios Árabes, Lingüística General y Documentación.
Keywords: Heródoto; Tucídides; Imperialismo; Oriente; Atenas